NEGOTIATING HAENYEO CULTURAL IDENTITY DURING JAPANESE COLONIZATION IN LISA SEE’S THE ISLAND OF SEA WOMEN - Marlina Sabalotok; Dian Eka Sari; Yuli Altri Rahmawangsih (LINGUA LITERA : journal of english linguistics and literature, 2026)
This study examines the representation of women’s cultural identity negotiation in Lisa See’s The Island of Sea Women from a postcolonial perspective. The novel offers an alternative portrayal of women during the Japanese colonial period in Korea, challenging dominant colonial narratives that often position women as passive victims of oppression. Through the experiences of the haenyeo characters, Mi-ja and Young-sook, the study explores how women actively preserved, negotiated, and reconstructed their cultural identity under colonial domination. Employing a qualitative textual analysis, this research draws on Homi K. Bhabha’s postcolonial theory to examine narrative elements, symbols, and character representations that reveal the dynamics of power relations between the colonizer and the colonized, as well as women’s strategies of symbolic resistance. The findings demonstrate that the female characters not only resisted colonial authority but also engaged in complex forms of cultural negotiation that led to the formation of a hybrid cultural identity. This hybrid identity enabled them to preserve indigenous cultural values while adapting to the social and political pressures of colonial rule, highlighting women’s agency in shaping identity under colonial conditions and contributing to discussions of gender and cultural identity in postcolonial contexts.